Hypolipidemic effect of [6]-Gingerol-loaded Eudragit polymeric nanoparticles in high-fat diet-induced rats and Gamma scintigraphy evaluation of gastric-retention time - Virendra Singh, Himanshu Pandey, Vatsala Misra, Vandana Tiwari, Pallavi Srivastava, Devendra Singh (Journal of Applied Pharmaceutical Science, 2022)
[6]-Gingerol is the potent pharmacological active phytocompound of ginger. The essential role of [6]-gingerol in drug therapy is limited due to its poor water solubility and low bioavailability. Hence, [6]-gingerol-loaded Eudragit nanoparticles were prepared by using a single emulsification solvent evaporation method to overcome hepatic firstpass metabolism and to increase oral bioavailability. The study was designed to investigate the anti-hyperlipidemic potential of [6]-gingerol in rats fed a high-fat diet (HFD). The hypolipidemic potential of [6]-gingerol at a dose of 25 and 50 mg/kg was evaluated in HFD-induced hyperlipidemic rats. The results of the study were surprisingly intriguing with [6]-gingerol significantly (p ≤ 0.005), altering the serum total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol levels to near-normal in HFD-induced hyperlipidemic rats. The TC and TG were also significantly reduced after treatment with 25 and 50 mg/kg of [6]-gingerol as compared to standard atorvastatin treatment. Gamma scintigraphy results were promising with 24-hour gastric-retention time. The novel formulation [6]-gingerol-loaded Eudragit polymeric nanoparticle has a significant potential to be used as a green antihyperlipidemic agent.
Keywords: [6]-Gingerol, Nanoformulation, Hypolipidemic, Atorvastatin, Gamma scintigraphy